ADDRESSING FOOD INSECURITY AMONG MALAYSIAN UNIVERSITY STUDENTS DURING COVID-19: IMPLICATIONS FOR ACADEMIC PERFORMANCE - Nor Farisya Hidayu Mohd Faidi; Ali, Asma'; Siti Nur’Afifah Jaafar; Nur Zalinda Zalbahar; Mohamad Rahijan Abdul Wahab (Malaysian Journal of Public Health Medicine, 2023)
University students are among the population that is most prone to experiencing food insecurity due to the COVID-19 pandemic. Students experiencing food insecurity have a higher likelihood of performing poorly at university. However, only a few studies have been conducted in Malaysia to determine the association between food insecurity, and academic performance among university students during COVID-19. As a result, the purpose of this study was to investigate the aforementioned association between variables. This cross-sectional study was conducted among 300 undergraduate students from Malaysia's selected public universities in each zone. This self-administered online survey is divided into three sections: demographic and socioeconomic factors; food security status via the USDA (food security survey module, FSSM); and students' current academic performance (based on ICGPA). SPSS version 25 was used to analyse the data. The result indicates the majority of the respondents were classified to have a marginal food security level (38.0%), followed by high food security level (31.0%), low food security level (21.7%), and the remaining (9.30%) were classified to have a very low food security level. The majority of respondents (45.3%) had a CGPA of 3.50 to 4.00. The study showed a statistically significant association between food insecurity and current CGPA among Malaysian university students (1, n=300) = 7.739 and p=0.021. The association between food insecurity and academic performance may be accounted for by a range of causes, including hunger, despair, and ill health. Selecting the extent to which each possible relationship between food insecurity and low academic performance contributes can aid health-related authorities in determining the most effective areas for intervention.